EXPORT PERFORMANCE IMPROVEMENT THROUGH MANAGEMENT AND TECHNOLOGY SUPPORT FOR SMEs CRAFT - Nugroho Mardi Wibowo; Yuyun Widiastuti; Siswadi Siswadi (UII, 2017)
Specific targets of this activity are: (i) SMEs can increase turnover; (ii) SMEs can enhance variety of design products; (iii) SMEs have skilled human resources on product design; (iv) SMEs can prepare financial statements; (v) SMEs have a standard quality assurance; (vi) SMEs can improve product quality and speed up the production process; (vii) Obtaining copyrights products. Methods of implementation of this program include: training and assistance with activities such as: the manufacture of machinery and production equipment, supply of equipment, participation in exhibitions, arrangement of storage space and show room, cooperating with other parties as well as the processing of copyright products. The results obtained from these activities, first with the brass foundry furnace and molds made of firebrick resulted in increased speed of production processes as well as fuel efficiency and cost of production for SME-1